uORF-mediated translation allows engineered plant disease resistance without fitness costs - Xu, Guoyong; Yuan, Meng; Ai, Chaoren; Liu, Lijing; Zhuang, Edward; Karapetyan, Sargis; Wang, Shiping; Dong, Xinnian (Nature (London), 2017)
WebIn both laboratory and field studies, engineering translational control of immune mediator production in Arabidopsis and rice confers disease resistance, without compromising plant fitness. Programming plant immunity It is well established that plants elicit immune responses by reprogramming their transcriptional response. Controlling this for agricultural purposes without reducing the plant's fitness has been a challenge. Xinnian Dong and colleagues have engineered translational control into Arabidopsis and rice to promote production of immune mediators and show, in laboratory and field studies, that this confers disease resistance without compromising plant fitness. This was achieved using insights from a related paper published in this issue, in which Xinnian Dong and colleagues uncover new regulators of plant immune responses. Through global translatome analysis, they observe that plants modify their translational output independently of the changes in the transcriptional output to establish pathogen-triggered immunity. Controlling plant disease has been a struggle for humankind since the advent of agriculture. Studies of plant immune mechanisms have led to strategies of engineering resistant crops through ectopic transcription of plants’ own defence genes, such as the master immune regulatory gene NPR1 (ref. 1 ). However, enhanced resistance obtained through such strategies is often associated with substantial penalties to fitness 2 , making the resulting products undesirable for agricultural applications. To remedy this problem, we sought more stringent mechanisms of expressing defence proteins. On the basis of our latest finding that translation of key immune regulators, such as TBF1 (ref. 3 ), is rapidly and transiently induced upon pathogen challenge (see accompanying paper 4 ), we developed a ‘TBF1-cassette’ consisting of not only the immune-inducible promoter but also two pathogen-responsive upstream open reading frames (uORFs TBF1 ) of the TBF1 gene. Here we demonstrate that inclusion of uORFs TBF1 -mediated translational control over the production of snc1-1 (an autoactivated immune receptor) in Arabidopsis thaliana and At NPR1 in rice enables us to engineer broad-spectrum disease resistance without compromising plant fitness in the laboratory or in the field. This broadly applicable strategy may lead to decreased pesticide use and reduce the selective pressure for resistant pathogens.